Assembling reduced graphene oxide hydrogel with controlled porous structures using cationic and anionic surfactants. (30th September 2019) - Hu, Yang; Xie, Xin; Sun, Chunbao; Kou, Jue
Abstract: The roles of cationic and anionic surfactants in assembling reduced graphene oxide hydrogels (RGOHs) and controlling their porous structures are studied in this work. The mechanisms of the surfactant effects were studied by x-ray diffraction, Fourier transform infrared spectroscopy, x-ray photoelectron spectroscopy, and electrochemical methods. The morphology and structure of graphene oxide and RGOH were examined by atomic force microscopy, scanning electron microscopy, and transmission electron microscopy. The experimental results showed that surfactants could modify the structure of as-prepared RGOH but did not change the chemical or physical properties of the reduced graphene oxide (RGO) sheets. The modification was achieved by changing the orientation of graphene oxide sheets in aqueous solutions. It was also found that RGOH could not be prepared in the presence of high dosages of cationic surfactant because the RGO sheets were stacked piecewise with just one orientation and could not be cross-linked at any angle. The presence of an anionic surfactant did not affect the formation of RGOH but only enlarged the pores in its cross-linking structure. In addition, RGOHs prepared with anionic surfactants were found to have a higher specific capacitance compared to RGOHs prepared with cationic surfactants.